Contribution of the multidisciplinary team of the better at home program in reversing a case considered palliative in the Municipality of Acreúna, Goias (GO) State, Brazil (Research, Society and Development, 2024)
This article aims to explore the contribution of the multidisciplinary team from the Melhor em Casa Program in reversing a case considered palliative in Acreúna, GO. It describes a retrospective case study of a patient admitted to the Melhor em Casa Program, in Acreúna - GO, on 08/08/2024, with Traumatic Brain Injury (TBI) and subdural hematoma. The patient also had comorbidities such as epilepsy, systemic arterial hypertension (SAH) and diabetes mellitus (DM). Due to the severity of his clinical condition, he was considered palliative and received nutritional support through Gastrostomy (GTT) and diseases with oxygenation and tracheostomy (TQT). The analysis was based on a review of the medical records, highlighting the work of the multidisciplinary team, made up of a doctor, nursing team, physiotherapy and nutritionist, who intervened to improve the patient's general condition. Throughout the treatment, a positive evolution was noted, with a direct impact on the patient's quality of life. The result of these interventions was significant, leading to the removal of the tracheostomy (TQT) and the reintroduction of oral feeding, demonstrating the success of specialized integrated care in the treatment of patients with multiple serious and delicate clinical conditions.